2017
DOI: 10.24926/iip.v8i2.506
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Health Information Sharing Behavior Using Social Media and Breast Cancer Screening

Abstract: Keywords: breast cancer screening; social media; health information sharing Introduction Social media, a means of electronic communication where users can share information and ideas online, is increasingly being used for sharing health information.1, 2 A Pew Research Center report found that 4 out of 10 people who commented on their health online have shared their personal health experiences online with others.3 Social media can increase engagement and access to health information to broader and more diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A significantly higher percentage of Hispanics (17.8%) and other races (27.0%) chose to share health information on social media compared to African Americans (8.6%) and Whites (12.9%). [38] After reviewing the 17 relevant original studies identified, we can conclude that the volume of breast cancer related social media is big enough to make it a good channel for reaching the target population.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher percentage of Hispanics (17.8%) and other races (27.0%) chose to share health information on social media compared to African Americans (8.6%) and Whites (12.9%). [38] After reviewing the 17 relevant original studies identified, we can conclude that the volume of breast cancer related social media is big enough to make it a good channel for reaching the target population.…”
Section: Discussionmentioning
confidence: 99%